Obesity-Driven Deficiencies of Specialized Pro-resolving Mediators May Drive Adverse Outcomes During SARS-CoV-2 Infection - Pal, Anandita; Gowdy, Kymberly M.; Oestreich, Kenneth J.; Beck, Melinda; Shaikh, Saame Raza (Frontiers in Immunology, 2020)
Obesity is a major independent risk factor for increased morbidity and mortality upon infection with Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2), which is responsible for the current coronavirus disease pandemic (COVID-19). Therefore, there is a critical need to identify underlying metabolic factors associated with obesity that could be contributing toward increased susceptibility to SARS-CoV-2 in this vulnerable population. Here, we focus on the critical role of potent endogenous lipid metabolites known as specialized pro-resolving mediators (SPMs) that are synthesized from polyunsaturated fatty acids. SPMs are generated during the transition of inflammation to resolution and have a vital role in directing damaged tissues to homeostasis; furthermore, SPMs display anti-viral activity in the context of influenza infection without being immunosuppressive. We cover evidence from rodent and human studies to show that obesity, and its co-morbidities, induce a signature of SPM deficiency across immunometabolic tissues. We further discuss how the effects of obesity upon SARS-CoV-2 infection are likely exacerbated with environmental exposures that promote chronic pulmonary inflammation and augment SPM deficits. Finally, we highlight potential approaches to overcome the loss of SPMs using dietary and pharmacological interventions. Collectively, this mini-review underscores the need for mechanistic studies on how SPM deficiencies driven by obesity and environmental exposures may exacerbate the response to SARS-CoV-2.